2018
DOI: 10.3389/fpls.2018.00437
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Light Signal Transduction Factors as a Means of Modifying Steroidal Glycoalkaloids Accumulation in Tomato Leaves

Abstract: Steroidal glycoalkaloids (SGAs) are cholesterol-derived specialized metabolites produced by Solanaceous plant species. They contribute to pathogen defense but are considered as anti-nutritional compounds and toxic to humans. Although the genes involved in the SGA biosynthetic pathway have been successfully cloned and identified, transcription factors regulating this pathway are still poorly understood. We report that silencing tomato light signal transduction transcription factors ELONGATED HYPOCOTYL 5 (SlHY5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 84 publications
0
39
0
Order By: Relevance
“…1B), further confirming the role of light in vindoline biosynthesis in C. roseus seedlings. Light is also known to affect the biosynthesis of other specialized metabolites, including SGA in tomato (Wang et al, 2018) and anthocyanins in a number of plant species (Liu et al, 2018). Consistent with leaf-specific vindoline accumulation, CrGATA1 and the five light-responsive vindoline pathway genes are preferentially expressed in aerial parts of the seedling (Fig.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…1B), further confirming the role of light in vindoline biosynthesis in C. roseus seedlings. Light is also known to affect the biosynthesis of other specialized metabolites, including SGA in tomato (Wang et al, 2018) and anthocyanins in a number of plant species (Liu et al, 2018). Consistent with leaf-specific vindoline accumulation, CrGATA1 and the five light-responsive vindoline pathway genes are preferentially expressed in aerial parts of the seedling (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…PIFs are known to interact with phytochromes and regulate lightresponsive gene expression in plants. PIFs regulate the biosynthesis of specialized metabolites, including anthocyanins (Shin et al, 2007;Liu et al, 2015) and SGAs (Wang et al, 2018). For anthocyanin biosynthesis in Arabidopsis, PIF3 and HY5 act as activators (Shin et al, 2007), whereas PIF4 and PIF5 function as repressors, as overexpression of PIF4 or PIF5 reduces anthocyanin accumulation (Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Plant SGAs are biosynthesized by a specific pathway, where the major player is the 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA), which catalyzes the first committed step of sterol precursors biosynthesis. Once formed, the precursors undergo several biochemical processes, such as hydroxylation, oxidation, transamination and glycosylation, before they produce SGAs [6]. The HMG-coding genes are highly regulated by both abiotic and biotic stressors, like light [7], hormones [8], wounding [9] and pathogens [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the bHLH motifs of Arabidopsis PIFs bind to specific sequence elements including G-boxes (CACGTG) and PIF binding E-boxes (ACATG; Martínez-García et al, 2000;Huq and Quail, 2002;Huq et al, 2004;Oh et al, 2007Oh et al, , 2009Kim et al, 2008;Leivar et al, 2008b;Hornitschek et al, 2009Hornitschek et al, , 2012Kidokoro et al, 2009;Li, 2012;Zhang et al, 2013;Li et al, 2014;Pfeiffer et al, 2014). Similarly, PIFs in other plant species including Sl-PIF1, Sl-PIF3, Os-PIL13, and Os-PIL14 also bind to G-boxes or promoters containing G-box or PIF binding E-box elements (Todaka, 2012;Cordeiro et al, 2016;Llorente et al, 2016;Sakuraba et al, 2017;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%